Invisible Hand of International Aid to Africa: The Geoeconomy of Deprivation (Economics and region, 2019)
In traditional societies the poor and the needy all had their place in the community, no questions asked about aid or assistance. The unfortunate needed the less fortunate and vice versa: mutual aid was a natural behavior and nobody ever thought of it in terms of assistance. Who would have imagined that the same word would one day often designate enslaving practices against persons in distress, or serve as a justification for governments to conduct military or repressive actions against their own people? The history of debates and practices around the concept of aid shows that the inconceivable has in fact become a reality.At a national or international level aid aims primarily at helping the alleged "donors" to maintain the devices that perpetuate their positions of power and social privileges, while depriving the poor of their own means to fight against poverty.We easily understand now why the promoters of major international meetings regularly held in favor of helping the poor – one of them which gathered Heads of States in March 2002 at Monterrey, Mexico, – carefully avoided any debate on the root causes of the production of misery and injustice. In fact, they are well aware that a careful examination of these cases would unveil the fraud perpetrated today worldwide under the brand of aid. Indeed, such a debate risks to disclose the perverse collusions, often structural, which, always in the name of aid, unify the leaders of the North and the South against their own "subjects". And when, for the sake of propaganda, the Northern "generous donors" threaten to reduce their "aid" on the grounds that the recipient governments are corrupt, this examination would eventually reveal all the machinery set up by these same donors to "help" these "rogue" governments rule over their own populations. Finally, a serious investigation of the underlying reasons for these maneuvers would demonstrate to the world opinion that the most of the aid destined to eligible poor countries is intended whether to strengthen military and coercive programs or to restructure their economies to be adapted to the requirements of the sole global market.Hence this bitter conclusion: what we insist on calling aid is but an expense to strengthen the structures that generate misery. However, the victims who are stripped of their real properties are never assisted since they seek to stand out from the global productive system in order to find alternatives in concert with their own aspirations.
Keywords: international economy; geoeconomics; deprivation; development; international assistance